Money-wise planner / Nur Syasya Qistina Suhari ... [et al.] - Suhari, Nur Syasya Qistina; Mohd Zainudin, Nini Suraya; Norazman, Alessa Syahira; Shahroni, Nur Izzah; Ariffin, Nurul Azrin (Universiti Teknologi MARA, Kedah, 2023)
Personal financial planning is crucial for everyone, but many people lack the knowledge and skills to manage their finances effectively. As a result, people often struggle with debt, financial insecurity and other related issues. To address this problem, we have created an innovative teaching aid in the form of a planner called “Money-Wise” that aims to help individuals to learn about personal financial planning while aligning their financial situation with their goals. Besides, the lack of financial literacy among the communities is a pressing issue that needs to be addressed. If not, they are at a risk of falling into debt, making poor financial decisions and facing financial hardship. The objective of this planner is to provide the individuals with a practical tool that can help them to learn about personal financial planning as well as to spread awareness regarding the needs in managing their finances. By using our planner, the communities can develop the skills and knowledge they need, to manage their finances effectively and make informed financial decisions. The uniqueness of our planner lies in its information regarding the financial information that an individual can trace and learn which will improve the user’s financial burden and eventually increase the economic security of the communities at large. The details that are included in the “Money-Wise” planner are balance sheet and cash flow that the user can use to start doing his/her financial planning. This will tremendously benefit those who do not have knowledge about financial planning. Apart from having a significant commercialization potential, it meets a critical need in the market for effective financial education tools which will improve the financial well-being of an individual who uses this innovative planner.